Analisis Dan Perancangan Aplikasi Monitoring On The Job Training (OJT) Smk Negeri 1 Boyolali Menggunakan Framework CodeIgniter: Analisis Dan Perancangan Aplikasi Monitoring On The Job Training (OJT) Smk Negeri 1 Boyolali Menggunakan Framework CodeIgniter - Widiyanti Kurnianingsih (The Indonesian Journal of Computer Science Research, 2022)
On Job Training (OJT) is the application of knowledge and skills acquired, and seeing their relevance in the world of work is an educational activity carried out by the company. To train students to improve their quality and be able to know the situation of the world of work is the goal of OJT. OJT activities are beneficial for agencies and students implementing OJT; meeting the needs of non-permanent employees with academic insight is one of them. PIECES analysis was carried out to identify problems at SMK NEGERI 1 BOYOLALI. Several conclusions can be drawn after going through the testing phase of the Monitoring on the Job Training (OJT) Application at SMK NEGERI 1 BOYOLALI. This system can assist field supervisors and school supervisors in carrying out all management, monitoring, reporting and assessment activities on the Job Training activities (OJT) and helping students manage attendance data and report on the Job Training (OJT) activities. Based on the explanation above, this research's focus is to build a website-based OJT using the CodeIgniter framework.